Patient involvement in quality improvement - a 'tug of war' or a dialogue in a learning process to improve healthcare? - Carolina Bergerum; Agneta Kullén Engström; Johan Thor; Maria Wolmesjö (BMC, 2020)
Abstract Background Co-production and co-design approaches to quality improvement (QI) efforts are gaining momentum in healthcare. Yet, these approaches can be challenging, not least when it comes to patient involvement. The aim of this study was to examine what might influence QI efforts in which patients are involved, as experienced by the patients and the healthcare professionals involved. Methods This study involved a qualitative design inspired by the constructivist grounded theory. In one mid-sized Swedish hospital's patient process organisation, data was collected from six QI teams that involved patients in their QI efforts, addressing care paths for patients with transient, chronic and/or multiple parallel diagnoses. Field notes were collected from participant observations during 53 QI team meetings in three of the six patient processes. Individual, semi-structured interviews were conducted with 12 patients and 12 healthcare professionals in all the six QI teams. Results Patients were involved in QI efforts in different ways. In three of the QI teams, patient representatives attended team meetings regularly. One team consulted patient representatives on a single occasion, one team collected patient preferences structurally from individual interviews with patients, and one team combined interviews and a workshop with patients. The patients' and healthcare professionals' expressions of what might influence the QI efforts involving patients were similar in several ways. QI team members emphasized the importance of organisational structure and culture. Furthermore, they expressed a desire for ongoing interaction between patients and healthcare professionals in healthcare QI. Conclusions QI team members recognised continuous dialogue and collective thinking by the sharing of experiences and preferences between patients and healthcare professionals as essential for achieving better matches between healthcare resources and patient needs in their QI efforts. Significant structural and cultural aspects of performing QI in complex hospital organisations were considered to be obstructions to progress. Therefore, to sustain learning and behaviour change through QI efforts at the team level, a deeper understanding of how structural and cultural aspects of QI promote or prevent success appears essential.